Evaluation of the performance of the CCD236 swept charge devices in lunar orbit using in-flight data - Jones, L.S.; Crews, C.; Endicott, J.; Holland, A.D. (Journal of instrumentation, 2022)
India’s Chandrayaan-2 Large Area Soft X-ray Spectrometer (CLASS) employs 16 CCD236 Swept Charge Devices (SCDs) similar in structure to Charge Coupled Device (CCD) image sensors. The CCD236 permits X-ray detection over a large surface area, intended to improve low flux performance, with simplified control interfaces and improved warm temperature performance. These devices were the subject of ground testing and performance evaluation before flight. Data that was recently made available by the Indian Space Research Organisation (ISRO) has permitted the analysis of the performance of the CLASS SCDs after over a year of operations around the Moon. Of particular interest is the change in device performance and behaviour during transit and in lunar orbit. Preliminary analysis has indicated that device FWHM, representing the aggregate of different noise sources, has increased in line with predictions based on ground irradiation and testing.